Back-to-Work Legislation Roundtable: Introduction - Smith, Charles W. (Labour / Le Travail, 2020)
Introduces the roundtable on back-to-work legislation held at the Canadian Association of Work and Labour Studies' annual conference in 2019. Summarizes the papers presented and pays tribute to the work of Leo Panitch and Donald Swartz.